Optimizing Operating Conditions to Increase the Effective Hydrogen Partial Pressure and Reduce Fresh Hydrogen in Vapor-Phase Cyclohexanol Production - Aisyah Hanunaida Yusriyyah; Rivan Pradipta Wibisono; Yulianazhwa Tiarawati (UPT Laboratorium Terpadu, Universitas Diponegoro, 2026)
Cyclohexanol is a vital intermediate in nylon precursor production, making its efficient synthesis highly relevant for large-scale chemical industries. Conventional processes often face inefficiencies such as excessive hydrogen consumption and poor energy utilization, which hinder economic viability. This study aims to optimize cyclohexanol production by improving hydrogen recovery and heat integration. Thermodynamic analysis confirmed the reaction is highly exothermic and favorable across the operating temperature range, emphasizing the need for strict thermal control. Process simulation was then employed to evaluate the baseline flowsheet and identify inefficiencies. A revised configuration was developed incorporating effluent cooling, vapor–liquid separation, and hydrogen recycling. The improved system significantly enhanced hydrogen efficiency, reactor performance, and energy utilization, leading to higher conversion rates and more stable operation. In conclusion, the optimized process demonstrates the importance of integrating reaction engineering with process-level design. The simulation framework also provides a foundation for future studies on intensified reactor–separator systems and advanced energy-saving strategies. Copyright © 2026 by Authors, Published by Universitas Diponegoro and BCREC Publishing Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).